2016
DOI: 10.1186/s40662-016-0047-5
|View full text |Cite
|
Sign up to set email alerts
|

Genetics in Keratoconus: where are we?

Abstract: Keratoconus (KC) is a non-inflammatory thinning and protrusion of the cornea in which the cornea assumes a conical shape. Complex etiology of this condition at present remains an enigma. Although environmental factors have been involved in KC pathogenesis, strong underlining genetic susceptibility has been proven. The lack of consistent findings among early genetic studies suggested a heterogeneity and complex nature of the genetic contribution to the development of KC. Recently, genome-wide linkage studies (G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
65
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(74 citation statements)
references
References 124 publications
4
65
0
3
Order By: Relevance
“…It is also expected that SNW1 and HDAC2 were contained in this meta-subnetwork as they were involved in notch signaling pathway which is down-regulated in keratoconus (You, et al, 2018). Interestingly, consistent with the associations between collagen genes and keratoconus (Bykhovskaya, et al, 2016), a novel collagens coding gene, COL1A1, was captured in this meta-subnetwork. Taken together, these shared gene interactions provided more valuable and general guides for drug repositioning and disease treatment as they characterized the common molecular mechanism among multiple KDDAs.…”
Section: Kddanet Uncovers the Shared Gene Interactions Underlying Mulsupporting
confidence: 62%
“…It is also expected that SNW1 and HDAC2 were contained in this meta-subnetwork as they were involved in notch signaling pathway which is down-regulated in keratoconus (You, et al, 2018). Interestingly, consistent with the associations between collagen genes and keratoconus (Bykhovskaya, et al, 2016), a novel collagens coding gene, COL1A1, was captured in this meta-subnetwork. Taken together, these shared gene interactions provided more valuable and general guides for drug repositioning and disease treatment as they characterized the common molecular mechanism among multiple KDDAs.…”
Section: Kddanet Uncovers the Shared Gene Interactions Underlying Mulsupporting
confidence: 62%
“…However, the results of this pilot study gave additional insight into the role of the Wnt signaling and/or focal adhesion pathways in KTCN development and showed the possible indications for further KTCN research. The identification of rare variants in different genes further supports the heterogeneity of KTCN with multiple genes underlying its pathogenesis Abu-Amero, Al-Muammar & Kondkar, 2014;Bykhovskaya, Margines & Rabinowitz, 2016;Mas Tur et al, 2017;Valgaeren, Koppen & Van Camp, 2018).…”
Section: Discussionmentioning
confidence: 72%
“…In our study, we found a new mutation (c.95 G > A) in LOX, accompanied by a reduction in LOX mRNA expression in KC patients. It can be well explained that destruction of normal LOX expression destroys ECM maturation by reduced cross-linking of collagen fibers in the cornea stroma, leading to cornea biomechanical instability and thinning 31,47 , which is a remarkable characteristic of KC. It can be further proved by observing reduced crosslinks between collagen and elastic fibers in LOX-null mice 48,49 .…”
Section: Discussionmentioning
confidence: 99%